2011
DOI: 10.1088/0954-3899/38/7/075101
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study on the α-decay fine structure of even–odd nuclei in the range 84 ⩽Z⩽ 102

Abstract: A systematic study on the α-decay fine structure of even-odd nuclei in the range 84 Z 102 is done for the first time using our recently proposed Coulomb and proximity potential model for deformed nuclei (CPPMDN). The external drifting potential barrier is obtained by the sum of deformed Coulomb potential, deformed two-term proximity potential and centrifugal potential. The computed half-lives and branching ratios are compared with the experimental values. The standard deviation of logarithmic half-lives and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The Coulomb and proximity potential model (CPPM) [41,42] and its modified version, the Coulomb and proximity potential model for deformed nuclei (CPPMDN) [43] is being used by the Santhosh et al, since the last decade for the cluster decay and alpha decay studies of heavy [44][45][46][47] and superheavy nuclei [48][49][50][51][52]. The recent studies on the α transitions from both the ground state and the isomeric states [53], α fine structure studies of eveneven [43], even-odd [54], odd-even [55] and odd-odd [56] nuclei, studies on the α decay half lives of the isotopes of Bi nuclei [47] and the theoretical predictions on the alpha decay chains of the isotopes of Z = 115 [49], 117 [50,51] and 119 [52] have proved the validity and applicability of both CPPM and CPPMDN. The present paper deals with an investigation on the cluster decay of eveneven clusters 4 He, 8 Be, 10 Be, 14 [30,31], the Universal (UNIV) curve of Poenaru et al [34,35] and the Scaling Law of Horoi et al [57] have been used for the comparison of our calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The Coulomb and proximity potential model (CPPM) [41,42] and its modified version, the Coulomb and proximity potential model for deformed nuclei (CPPMDN) [43] is being used by the Santhosh et al, since the last decade for the cluster decay and alpha decay studies of heavy [44][45][46][47] and superheavy nuclei [48][49][50][51][52]. The recent studies on the α transitions from both the ground state and the isomeric states [53], α fine structure studies of eveneven [43], even-odd [54], odd-even [55] and odd-odd [56] nuclei, studies on the α decay half lives of the isotopes of Bi nuclei [47] and the theoretical predictions on the alpha decay chains of the isotopes of Z = 115 [49], 117 [50,51] and 119 [52] have proved the validity and applicability of both CPPM and CPPMDN. The present paper deals with an investigation on the cluster decay of eveneven clusters 4 He, 8 Be, 10 Be, 14 [30,31], the Universal (UNIV) curve of Poenaru et al [34,35] and the Scaling Law of Horoi et al [57] have been used for the comparison of our calculations.…”
Section: Introductionmentioning
confidence: 99%
“…authors adopted a simple barrier penetration approach to calculate α-decay branching ratios for even-even nuclei. Further calculations of α decays to ground and excited states were carried out for heavy deformed nuclei in the UMADAC [48] and in the CPPMDN [33][34][35]. All these approaches treated α decay as a one-dimensional problem and worked in the framework of the semiclassical WKB approximation.…”
Section: Coupled-channel Calculations For α-Decay Fine Structurementioning
confidence: 99%
“…Nowadays the new challenge in α-decay studies is the understanding of the α-decay fine structure observed in heavy deformed nuclei. It has been investigated from both semiclassical and coupled-channel standpoints [31][32][33][34][35][36][37][38][39]. Besides, α decay can proceed from excited states of parent nuclei if it competes with γ transitions.…”
Section: Introductionmentioning
confidence: 99%
“…So far different theoretical models such as shell model, the fission like model, and the cluster model have been used to determine the potential barrier governing the alpha decay process [8][9][10][11][12][13][14][15]. The role of some important factors like the shell effects have been studied by Tonozuka and Arima [16] and the fine structure of alpha decay has been reported by Santhosh et al [17]. Moreover, Royer taking account of the role of angular momentum, proposed analytic formulas for alpha decay half life [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Royer taking account of the role of angular momentum, proposed analytic formulas for alpha decay half life [18]. Deformation is also an important factor and various models incorporated the effects of deformation and orientation on the interaction potential [12,15,17,19]. In the present work, in order to consider the effect of deformation and orientation degrees of freedom, we perform calculations in the frame work of coulomb and proximity potential model for deformed nuclei [20].…”
Section: Introductionmentioning
confidence: 99%